Effects of water-soluble and in-feed organic acids on the growth performance of weanling pigs - Gottlob, R.O.; Neill, C.R.; Groesbeck, C.N.; Schneider, J.D.; Frantz, N.Z.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 360 weanling pigs (initially 11.5 lb and 18 ± 3 d of age, PIC) were used in a 42-d growth assay to determine the effects of water-soluble antimicrobials and organic acids in feed and/or water on nursery pig growth performance. Pigs were allotted to one of 9 experimental treatments: 1) control (no feed or water antimicrobials or acids); 2) water containing 38 mg/L neomycin sulfate; 3) water containing 0.06% Activate3 WD; 4) water containing 0.12% Activate WD; 5) feed containing Neo-Terramycin4 (140 g/ton neomycin sulfate, 140 g/ton oxytetracycline HCl; neo/oxy); 6) feed containing 0.50% Activate DA; 7) feed containing 0.45% Starter L; 8) feed containing 0.45% Multimax L; and 9) feed containing 0.50% Activate DA and 0.10% Mintrex3 P. Overall (d 0 to 42 after weaning), pigs provided neo/oxy in the feed had greater (P<0.05) ADG, compared with pigs in all other treatments, except the pigs provided the combination of Activate DA and Mintrex P in the feed. Pigs provided neo/oxy in the feed had greater ADFI (P<0.02) than did pigs provided the control treatment. There were no differences in feed efficiency between any of the treatments. These data demonstrate that pigs provided in-feed antimicrobials had improved growth, whereas those provided organic acids in feed and water did not.
Keywords: Nursery pig; Antimicrobials; Organic acids; Water; Growth; Swine